PENGARUH COMPETITOR ACCOUNTING TERHADAP KEUNGGULAN BERSAING DAN KINERJA ORGANISASI - Astuti, Mona; Azmi, Zul; Darwin, Ranti (Research in Accounting Journal (RAJ), 2020)
The purpose of this study was to know the affect of Competitor Accounting as a Strategic Management Accounting Techniques towards Competitive Adventage and Organization Performance. On business culinary in Pekanbaru. This study used a questionnaire to obtain primary data with a sample size of 38 respondents and was tested using path modeling analysis techniques. From the examination showed that there were positive affect of Competitor Accounting as a Strategic Managemengt Acounting Techniques towards Competitive Adventage, negative affect of Competitor Accounting as a Strategic Managemengt Acounting Techniques towards Organization Performance, positive affect of Competitive Adventage towards Organization Performance, and positive indirectly affect of Competitor Accounting as a Strategic Managemengt Acounting Techniques towards Organization Performance with Competitive Adventage mediation.